2006
DOI: 10.1387/ijdb.052106ym
|View full text |Cite
|
Sign up to set email alerts
|

Two modes of action by which Xenopus hairy2b establishes tissue demarcation in the Spemann-Mangold organizer

Abstract: The Hairy and Enhancer-of-Split (HES) family of transcriptional repressors plays important roles in pattern formation during development throughout the animal kingdom. Generally, HES proteins repress the expression of genes specific for neighboring tissues to maintain the nature of cells expressing HES proteins, resulting in pattern formation. Xhairy2b, a Xenopus HES, establishes the prospective anterior prechordal mesoderm identity in the Spemann-Mangold organizer by both inducing specific genes and repressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…For example, Hairyrelated proteins may function as dual transcriptional regulators (activator and repressor) in embryonic axis formation (Murato et al, 2006). In the ascidian embryo, Posterior end mark (PEM), which has a WRPW motif and lacks a DNA-binding domain, plays a role in anteroposterior patterning (Yoshida et al, 1996).…”
Section: Research Articlementioning
confidence: 99%
“…For example, Hairyrelated proteins may function as dual transcriptional regulators (activator and repressor) in embryonic axis formation (Murato et al, 2006). In the ascidian embryo, Posterior end mark (PEM), which has a WRPW motif and lacks a DNA-binding domain, plays a role in anteroposterior patterning (Yoshida et al, 1996).…”
Section: Research Articlementioning
confidence: 99%
“…In the pancreas, Hes1 is involved in antagonizing the function of B-class bHLH proteins such as Ngn3, and is expressed in undifferentiated precursor cells (Jorgensen et al, 2007). In Xenopus, Hes1 is known as hairy2b and it has been extensively studied in the context of neural development (Yamaguti et al, 2005; Murato et al, 2006). Within the pancreas, it is expressed in a punctate fashion from the earliest stages, most likely marking pancreatic progenitor cells (data not shown).…”
Section: Pancreatic Specification (After Nf30)mentioning
confidence: 99%
“…This, in turn, means that Xhairy2 overexpression around the LF region should increase the LF expression of pax6 and six3. However, neither wildtype Xhairy2 overexpression nor engrailed-fused form of Xhairy2 overexpression (Murato et al, 2006) increased the LF expression of six3 (data not shown). Moreover, our data showed that Xhairy2 knockdown did not alter the expression of fgf8 or fgfr4c (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Since both Xhairy2a and Xhairy2b function as transcriptional repressors, similar to other Hes proteins (Murato et al, 2006(Murato et al, , 2007, we assumed that the up-regulation of genes that are not expressed in the future LF region at gastrula or early neurula stage might block LF formation at mid-neurula stage. In our previous study of the functions of Xhairy2 in neural crest formation , we showed that Xhairy2 downregulated subsets of proneural marker genes, such as X-delta-1 (Chitnis et al, 1995) and X-ngnr-1 .…”
Section: Loss Of Pax6 Expression In Lens Region Is Partly Caused By Ementioning
confidence: 99%